Optimal IP Current Controller Design Based on Small Signal Stability for THD Reduction of a High-Power-Density PFC Boost Converter - Ahmed H. Okilly; Hojin Jeong; Jeihoon Baek (Applied Sciences, 2021)
This paper presents an optimal design for the inner current-control loop of the continuous current conduction mode (CCM) power factor correction (PFC) stage, which can be used as the front stage of the two-stage AC/DC telecom power supply. The conventional single-phase CCM-PFC boost converter is implemented with proportional–integral (PI) controllers in both the voltage and current-control loops to regulate the output DC voltage to the specified value and to ensure the input current follows the input voltage, which offers a converter with a high-power factor (PF) and low current total harmonic distortion (THD). However, due to the slow dynamic response of the PI controller at the zero-crossing point of the input supply current, the input current cannot fully follow the input voltage, which leads to high THD. In this paper, we investigate a digitally controlled PFC converter with an optimally designed inner current-control loop using a doubly-fed control loops integral-proportional (IP) controller to reduce the THD and to offer an input current with a unity PF. For the economic design of a digitally controlled PFC converter, two isolated AC and DC voltage sensors are designed for interfacing with the microcontroller unit (MCU). PSIM software as well as experimental prototype was used to test the converter performance using the proposed designed current controllers and isolated voltage sensors. We achieved a high-power-density, digitally controlled, telecom PFC stage with a power factor more than 99% and THD of about 5.50%.